Pencegahan Fraud dalam Pengelolaan Keuangan Desa - Atmadja, Anantawikrama Tungga; Saputra, Adi Kurniawan (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 12 No 1 (2017)DO - 10.24843/JIAB.2017.v12.i01.p02, 2017)
This study aimed to examine the effect of variable competence of personnel and internal control systems to the prevention of fraud in the management of village finances with morality as a moderating variable. This study uses the questionnaire survey, the number of samples used were 57 villages receive funding villages in Buleleng. Analysis of data using multiple linear regression and Moderated Regression Analysis (MRA). The results showed that the competence of personnel and internal control systems significant effect on the prevention of fraud village financial management, as well as the moderating influence of morality proven competence of personnel and internal control systems to the prevention of fraud in the management of village finances.
Keywords: Kompetensi aparatur, sistem pengendalian internal, fraud, keuangan desa, dan moralitas